Geriatric psycho-oncology : a quick reference on the psychosocial dimensions of cancer symptom management - Holland, Jimmie C.; Wiesel, Talia Weiss; Nelson, Christian J.; Roth, Andrew J.; Alici, Yesne (APOS Clinical Reference Handbooks., 2015)
Geriatric Psycho-Oncology is a comprehensive handbook that provides best practice models for the management of psychological, cognitive, and social outcomes of older adults living with cancer and their families. Chapters cover a wide range of topics including screening tools and interventions, psychiatric emergencies and disorders, physical symptom management, communication issues, and issues specific to common cancer sites. A resource section is appended to provide information on national services and programs. This book features contributions from experts designed to help clinicians review,